2003
DOI: 10.1097/00061198-200308000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 0.005% Latanoprost on Ocular Anterior Structures and Ciliary Body Thickness

Abstract: The increase of ciliary body thickness, which was measured in vivo by ultrasound biomicroscopy and associated with the intraocular pressure-lowering effect, indirectly supports the mechanism of uveoscleral outflow enhancement induced by latanoprost. These data are in agreement with the biochemical hypothesis of the passage of the aqueous flow through the extracellular spaces of the ciliary muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…It was reported that increase of ciliary body thickness was correlated with the IOP-lowering effect of antiglaucoma drugs. 13 In the current study, though IOP-lowering agents were used in all of the APAC eyes (no laser or surgical procedures were performed), ciliary body thickness decreased in APAC eyes. Moreover, higher IOP associated with thinner ciliary body could still be detected.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…It was reported that increase of ciliary body thickness was correlated with the IOP-lowering effect of antiglaucoma drugs. 13 In the current study, though IOP-lowering agents were used in all of the APAC eyes (no laser or surgical procedures were performed), ciliary body thickness decreased in APAC eyes. Moreover, higher IOP associated with thinner ciliary body could still be detected.…”
Section: Discussionmentioning
confidence: 72%
“…14 Ciliary body thickness at the point of the scleral spur (CBT0) 14 and at the distance of 1000 lm (CBT1000) from the scleral spur is defined as described previously. 13 Anterior placement of ciliary body (APCB) is the distance from the most anterior point of ciliary body to the vertical line from the inner wall of the sclera through the scleral spur 14 ; trabecular-ciliary angle (TCA) is the angle between the posterior corneal surface and the anterior surface of the ciliary body. 15 is and the greater the LV is, the thinner the ciliary body is and the more it is anteriorly located.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marchini G et al 68 assessed the effects of 0.005% latanoprost on the anterior segment geometry and ciliary body thickness using ultrasound biomicroscopy.…”
Section: Effects Of Drugsmentioning
confidence: 99%